The Influence of Employee Engagement and Organizational Citizenship Behavior on Employee Performance Laboratory Division: JEL Classification: J24, M12, M51, M54, D23 - Irma Wati; Muliyadi Hamid; Syamsuddin Bidol (Newinera Publisher, 2025)
The nickel mining industry faces significant challenges in maintaining employee performance amidst high work demands and a complex work environment. One strategy that can be implemented is to enhance employee engagement and organizational citizenship behavior (OCB). This study aims to analyze the influence of employee engagement and OCB on the performance of employees in the Laboratory Division of PT Obsidian Stainless Steel. This research was conducted in 2025 using a quantitative approach with multiple linear regression analysis techniques. The sample consisted of 134 employees selected through random sampling. Data were collected through questionnaires and documentation. The results show that employee engagement has a significant partial effect on performance (p = 0.000), as does OCB (p = 0.002). Simultaneously, employee engagement and OCB have a positive and significant effect on employee performance (p = 0.001 < 0.05). The adjusted R² value of 0.593 indicates that 59.4% of the variation in performance can be explained by these two variables, while the remaining 40.6% is influenced by other factors outside this study.